2002
DOI: 10.1136/bmj.325.7359.305
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, childhood socioeconomic environment, and cognitive development in the 1958 British birth cohort study

Abstract: Objectives To examine the combined effect of social class and weight at birth on cognitive trajectories during school age and the associations between birth weight and educational outcomes through to 33 years. Design Longitudinal, population based, birth cohort study. Participants 10 845 males and females born during 3-9 March 1958 with information on birth weight, social class, and cognitive tests. Main outcome measures Reading, maths, draw a man, copying designs, verbal and non-verbal ability tests at ages 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
4
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(210 citation statements)
references
References 18 publications
16
187
4
3
Order By: Relevance
“…Although at the level of concepts, the researchers in the McGill lab would probably go some way along with this interpretation of genomes in context, their everyday research practice certainly looks very different. Consider one ongoing project in the lab: the lab collaborates with British epidemiologists in charge of the 1958 cohort (for example, Jefferis et al, 2002), a large cohort of children born in 1958 in Britain. Socio-economic data exist from birth to age 40 and blood samples exist at age 40.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…Although at the level of concepts, the researchers in the McGill lab would probably go some way along with this interpretation of genomes in context, their everyday research practice certainly looks very different. Consider one ongoing project in the lab: the lab collaborates with British epidemiologists in charge of the 1958 cohort (for example, Jefferis et al, 2002), a large cohort of children born in 1958 in Britain. Socio-economic data exist from birth to age 40 and blood samples exist at age 40.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…3,[9][10][11] At first glance, this might suggest a role of biological factors in favor of environmental factors in this association. Gender-related difference, however, may challenge this interpretation and suggests that part of the association between low birth weight and educational level is attributable to adverse early circumstances.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4] However, previous studies of general populations suggested that birth weight is associated with cognition and educational attainment across the full birth weight range. 3 The association between low birth weight or small for gestational age and cognitive achievement has been found to be independent of social background, 3,9,10 although some studies suggest that a contribution of birth weight in cognitive achievement including school and educational achievement is confounded by other factors such as socioeconomic status 11 or childhood home and learning environment. 10 In addition, there are inconsistencies that compromise the evidence on an association between low birth weight and educational achievement.…”
mentioning
confidence: 99%
“…Children born to generally lower SES and teenage mothers appear to be at increased risk for impaired of lower IQ scores (Kenny, 1995) and poorer linguistic outcomes (Spieker & Bensley, 1994). Data from the 1958 British Birth Cohort Study (Jefferis, Power, & Hertzman, 2002) indicates that class inequalities in cognitive ability increase over the life course. Turley (1999) suggests that maternal age at first birth is significantly associated with cognitive test scores of firstborn children as well as those from subsequent births, however conflicting evidence has been provided by Geronimus, Korenman, and Hillemeier (1994).…”
Section: S E S and Cognitive Developmentmentioning
confidence: 99%